2021
DOI: 10.1038/s41590-021-01049-2
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of maternal SARS-CoV-2 infection on the immunology of the neonate

Abstract: Despite extensive studies into severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the effect of maternal infection on the neonate is unclear. To investigate this, we characterized the immunology of neonates born to mothers with confirmed SARS-CoV-2 infection during pregnancy. Here we show that maternal SARS-CoV-2 infection affects the neonatal immune system. Despite similar proportions of B cells, CD4 + T cells and CD8 + T cells, increased percentages of natural killer cells, Vδ2 + γδ T cells and re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
88
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 53 publications
11
88
1
Order By: Relevance
“…A polyfunctional cytokine response refers to the ability of a cell population to produce multiple cytokines at once (such as TNF, IFN-γ and IL-17) and represents a marker of cellular activation and maturation, as well as a correlate of protective immunity when specifically targeted to a virus 4 . The increased T cell cytokine functionality noted by Gee et al was evaluated in a subset of neonates and was found not to be specific for SARS-CoV-2 peptides in seven of eight neonates (88%) 3 . These data indicate that fetal immune imprinting due to a maternal SARS-CoV-2 infection during pregnancy is probably not a result of direct exposure to the virus and is instead a result of fetal exposure to an inflammatory environment.…”
Section: Gee Et Al Demonstrate That Neonatesmentioning
confidence: 93%
See 4 more Smart Citations
“…A polyfunctional cytokine response refers to the ability of a cell population to produce multiple cytokines at once (such as TNF, IFN-γ and IL-17) and represents a marker of cellular activation and maturation, as well as a correlate of protective immunity when specifically targeted to a virus 4 . The increased T cell cytokine functionality noted by Gee et al was evaluated in a subset of neonates and was found not to be specific for SARS-CoV-2 peptides in seven of eight neonates (88%) 3 . These data indicate that fetal immune imprinting due to a maternal SARS-CoV-2 infection during pregnancy is probably not a result of direct exposure to the virus and is instead a result of fetal exposure to an inflammatory environment.…”
Section: Gee Et Al Demonstrate That Neonatesmentioning
confidence: 93%
“…A striking finding by Gee et al was that some changes in fetal immunity associated with maternal COVID-19 were time dependent 3 . Perturbations in the frequency of neonatal NK cells and Vδ2 + γδ T cells seemed to recover with a longer interval between maternal COVID-19 and birth.…”
Section: Gee Et Al Demonstrate That Neonatesmentioning
confidence: 98%
See 3 more Smart Citations